Gender and Migration: Resisting with a Camera. A Researcher to Researcher Experience - Hernández-Albújar, Yolanda; Ciccaglione, Adriana (Imaginations)

(untitled) (York University, 2022)
This manuscript is a reflexive collaboration between two differently situated researchers. It meets at the crossroad of knowledge and visual activism at three levels: it uses a case study to analyze the possibilities of photovoice as a form of resistance against narratives of hate; it reflects on the ways in which the observed and the observer cooperate to construct from their own perspectives a legitimized knowledge aiming to promote visibility and social transformation; finally, it revises whether photovoice may become a form of visual activism and, if so, the ways in which images may be used toward this goal. Using as a point of departure the work of the photographer Diane Arbus and a photovoice project on being a migrant woman in Spain, the authors elaborate on the power of images to work at the margins, from the margins, and for the margins.